Digital Elevation Models : A Guidance Note on How Digital Elevation Models are Created and Used - Includes Key Definitions, Sample Terms of Reference, and How Best to Plan a DEM-Mission - Croneborg, Louise; Saito, Keiko; Matera, Michel; McKeown, Don; van Aardt, Jan (World Bank, Washington, DC, 2020)
Digital elevation models (DEMs) represents the elevation of the earth’s surface in the form of a digital image where each pixel contains an elevation value of the center point of the pixel. DEMs are a primary input to any modeling or process quantification involving the earth’s topography and are used across several areas of development. Access to elevation, and slope maps enable responders to assess where floods will infill the landscape, create inaccessible areas, or create health risks, example, cholera. DEMs are also used prominently in infrastructure planning and mapping; road design and construction for transportation; urban environmental planning to assess construction, drainage, and green landscaping; agriculture planting and irrigation strategies; ecological modeling to assess ecosystem flora and fauna; and geological applications such as seismic and coastal monitoring. Accurate elevation information is therefore key for a wide range of development projects related to poverty reduction, urban development, water management, and other concerns. Thus, the ability to design and commission or acquire DEMs is increasing in relevance across the globe. This DEMs guidance note aims to: (a) provide sufficient information to understand the overall processes involved in the acquisition of DEMs and their uses, and (b) inform and guide the decision-making criteria; different design and implementation strategies; and options and costs that exist when acquiring DEMs.